Treatments for colorectal liver metastases: A new focus on a familiar concept. (December 2016) - Zampino, M.G.; Magni, E.; Ravenda, P.S.; Cella, C.A.; Bonomo, G.; Della Vigna, P.; Galdy, S.; Spada, F.; Varano, G.M.; Mauri, G.; Fazio, N.; Orsi, F.
Abstract: A major challenge for the management of advanced-colorectal-cancer is the multidisciplinary approach required for the treatment of liver metastases. Reducing the burden of liver metastases with liver-directed therapy has an important impact on both survival and health-related quality of life. This paper debates the rationale and current liver-directed approaches for colorectal liver metastases based on the evidence of literature and new clinical trials. Surgery is the gold standard, when feasible, and it's the main treatment goal for patients with potentially-resectable disease as a means of prolonging progression-free survival. Better tumor response rates with modern systemic therapy mean that more unresectable patients are now down-staged for radical resection following conversion therapy but for other patients, additional procedures are needed. In multiple unilobar disease, when the projected remnant liver is <30% of the total liver, portal embolization or selective-internal-radiation-therapy (SIRT) can induce hypertrophy of the healthy liver, leading to resectability. In multiple bilobar disease, in situ destruction of non-resectable lesions by minimally invasive techniques may be associated with liver resection to achieve potential curative intent. Other palliative liver-directed approaches, such as SIRT or intra-hepatic chemotherapy (HAI), which are associated with higher response rates, may also have role in down-staging patients for resection. Until recently, such technologies have not been validated in prospective controlled trials. However in the light of new Phase 3 data for SIRT as well as for HAI combined with modern therapies or radiofrequency ablation in the first- and second-line setting, the clinical value of these treatments needs to be re-appraised.